ANALISIS FRASA ENDOSENTRIK KOORDINATIF DAN FRASA ENDOSENTRIK APOSITIF DALAM NOVEL JAIS DARGA NAMAKU KARYA AHDA IMRAN KAJIAN SINTAKSIS - Bakir Hasyim Bakir Hasyim; Ali Manshur Ali Manshur (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2023)
The context of this study is an analysis of coordinate and apositive endocentric phrases in the novel Jais Darga Namaku by Ahda Imran. Phrases are not only found in scientific or non-fiction works but also in works of fiction or literary works such as in short stories and novels. Among them is a novel by Ahda Imran entitled Jais Darga Namaku. The novel Jais Darga Namaku tells the story of the life journey of an Indonesian woman with all her ambitions. That ambition made her known as Jais Darga or Madam Darga, an international art dealer in Paris. It was this ambition that kept Jais wandering to many distant lands, that he could no longer tell whether he was "away" or "home". In this study using a qualitative approach with a type of descriptive qualitative research with data collection using the listen to record method. The selected data are primary data and secondary data. Data analysis uses Sugiyono analysis, namely data reduction, data presentation, and conclusions, while data validity techniques use triangulation, including: source triangulation, engineering triangulation, and time triangulation. The results of the study found were coordinated, and apositive endocentric phrases. The coordinating endocentric phrase found in Ahda Imran's novel Jais Darga Namaku has three parts, the first 51 coordinative endocentric phrases, the second 51 "and" connectors, the third 7 coordinate endocentric phrases, the coordinate endocentric phrases that do not use 4 connectors. Apositive endocentric phrases found in the novel Jais Darga Namaku by Ahda Imra as many as 16. So the analysis of coordinate and apositive endocentric phrases is proven in the novel Jais Darga Namaku by Ahda Imran.